ITERATIVE NUMERICAL-SOLUTION OF SCATTERING PROBLEMS - Tomio, L.; Adhikari, S. K. (Elsevier B.V., 1995)
An iterative Neumann series method, employing a real auxiliary scattering integral equation, is used to calculate scattering lengths and phase shifts for the atomic Yukawa and exponential potentials. For these potentials the original Neumann series diverges. The present iterative method yields results that are far better, in convergence, stability and precision, than other momentum space methods. Accurate result is obtained in both cases with an estimated error of about 1 in 10(10) after some 8-10 iterations.